The democratic lessons learned: how experiences of (un-)equal treatment in school influence satisfaction with democracy in later life - Weiß, Julia; Parth, Anne-Marie (Zeitschrift für Politikwissenschaft, 2022)
Previous studies have shown that economic and political experiences influence the level of satisfaction with democracy; however, they fail to explain whether these experiences have the same effect for everyone, whether there is interindividual variance and where these differences might be rooted. In this article, we investigate these roots of interindividual variance and base our argument on the observation that early experiences in school are formative and influence the effect of economic and political experiences on satisfaction with democracy. We analyze an original representative dataset on the German population to test how school experiences, more precisely equal treatment in school, interact with economic and political experiences in later life and thereby influence satisfaction with democracy. We find that school experiences play a significant role here. Voting for the governing parties especially increases satisfaction with democracy if respondents were treated equally in school. Similarly, past experiences of unemployment in particular decrease people’s levels of satisfaction with the political system if they were not treated equally in school. The findings highlight that early experiences made in school can have a relevant influence on satisfaction with democracy in later life.
Gesehen am 13.03.2023